CARTOGRAPHIC SOURCES USED IN THE CREATION OF AGRICULTURAL ELECTRONIC CARDS - RUSTAM KAMARIDDINOVICH OYMATOV (International Journal of Innovations in Engineering Research and Technology, 2021)
The purpose of the study is to develop geoinformation support for electronic maps of agricultural design at the level of an individual agricultural enterprise. Research is carried out in the conditions of the Republic of Uzbekistan. To achieve this goal in a scientific article, the following tasks are solved: to consider the scientific foundations of the territorial organization of agricultural production on a landscape basis using geographic information systems and technologies; to substantiate the conceptual GIS model of electronic maps of agricultural design at the level of an individual agricultural enterprise; to develop a methodology and a general algorithm for creating and using a system of electronic maps in the process of agrolandscape design; develop a geodatabase structure for analysis; to assess the effectiveness of the use of GIS technologies for electronic maps of agricultural design.